Glandular Odontogenic Cyst in Dentigerous Relationship: An Uncommon Case Report - Jean Carlos Barbosa Ferreira; Eneida Franco Vêncio; Rodrigo Tavares de Sá; Giovanni Gasperini (Case Reports in Dentistry)
Glandular odontogenic cyst (GOC) is an uncommon cyst of the jaw. Less than 200 cases are reported in the literature, and only 22 cases are associated with an unerupted tooth (dentigerous relationship). Although it is an asymptomatic lesion, it can be destructive and has high recurrence rates. The diagnosis can be especially challenging due to the lack of distinct diagnostic clinic-radiological criteria and nonspecific microscopic features, mimicking benign and malignant lesions. Conservative surgical treatment has been the choice for most surgeons, but marginal or partial jaw resection has been reported. This report describes a rare case of GOC in a dentigerous relationship, which was treated with enucleation and peripheral osteotomy.